Process of adhesion of the Adequate Childbirth Program to improve obstetric care in private hospitals in Brazil - Débora Cecília Chaves de Oliveira; Andreza Rodrigues; Lucia Regina de Azevedo Nicida; Maysa Luduvice Gomes; Jacqueline Alves Torres; Elyne Montenegro Engstrom (BMC, 2023)
Plain language summary In 2015, a quality improvement program, called the "Adequate Childbirth Program" (PPA), was recommended by the National Supplementary Health Agency so that Brazilian private hospitals could, through a change in the care model, reduce unnecessary cesarean sections and stimulate the natural and safe process in childbirth. The process of adhering to the PPA was studied in this article. Ten managers and 24 assistant leaders were interviewed in 08 private hospitals in Brazil. The main reasons for joining the PPA were the absence of other quality improvement programs; for being a program considered necessary in the country's midwifery, which could increase the prestige of hospitals in the view of women and families; for proposing an improvement in the quality of care; and for stimulating of structural and ambiance reforms. Social, cultural, and economic values motivated hospital adherence. The invitation strategy used by the PPA coordination, through socially respected members in Brazil, such as medical professionals, was highly valued by the hospital's leaders and encouraged adherence to the Program.